Maternal exposure to air pollution alters energy balance transiently according to gender and changes gut microbiota - Zordão, Olivia Pizetta; Campolim, Clara Machado; Yariwake, Victor Yuji; Castro, Gisele; Ferreira, Clílton Kraüss de Oliveira; Santos, Andrey; Norberto, Sónia; Veras, Mariana Matera; Saad, Mario Jose Abdalla; Saldiva, Paulo Hilário Nascimento; Kim, Young-Bum; Prada, Patricia Oliveira (Frontiers in Endocrinology, 2023)
We aimed to determine the most critical period of maternal exposure to particulate matter (PM2.5) that impairs offspring's energy metabolism and gut microbiota composition. Unexposed female and male C57BL/6J mice were mated. PM2.5 or filtered air (FA) exposure occurred only in gestation (PM2.5/FA) or lactation (FA/PM2.5). We studied the offspring of both genders. PM2.5 exposure during gestation increased body weight (BW) at birth and from weaning to young in male adulthood. Leptin levels, food intake, Agrp, and Npy levels in the hypothalamus were also increased in young male offspring. Ikbke, Tnf increased in male PM2.5/FA. Males from FA/PM2.5 group were protected from these phenotypes showing higher O2 consumption and Ucp1 in the brown adipose tissue. In female offspring, we did not see changes in BW at weaning. However, adult females from PM2.5/FA displayed higher BW and leptin levels, despite increased energy expenditure and thermogenesis. This group showed a slight increase in food intake. In female offspring from FA/PM2.5, BW and leptin levels were elevated. This group displayed higher energy expenditure and a mild increase in food intake. To determine if maternal exposure to PM2.5 could affect the offspring’s gut microbiota, we analyzed alpha diversity by Shannon and Simpson indexes and beta diversity by the Linear Discriminant Analysis (LDA) in offspring at 30 weeks. Unlike males, exposure during gestation led to higher adiposity and leptin maintenance in female offspring at this age. Gestation exposure was associated with decreased alpha diversity in the gut microbiota in both genders. Our data support that exposure to air pollution during gestation is more harmful to metabolism than exposure during lactation. Male offspring had an unfavorable metabolic phenotype at a young age. However, at an older age, only females kept more adiposity. Ultimately, our data highlights the importance of controlling air pollution, especially during gestation.